2017
DOI: 10.1109/lpt.2017.2711780
|View full text |Cite
|
Sign up to set email alerts
|

100-Gb/s Transmission Over a 2520-km Integrated MCF System Using Cladding-Pumped Amplifiers

Abstract: Abstract-A 10.5 Tbit/s optical transmission (15 x 100 Gbit/s QPSK channels per core) over 2,520 km of multicore fiber is achieved using an integrated multicore transmission link consisting of directly spliced multicore components such as fan-in/fanout fiber couplers, a 60 km trench-assisted 7-core hexagonal fiber and cladding-pumped erbium-ytterbium-doped fiber amplifiers.Index Terms-Space division multiplexing, multicore fiber, cladding-pumped multicore amplifier, long-haul transmission, integrated multicore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…In multi-core transmissions, cladding pumping avoids spatial channel demultiplexing/multiplexing at the amplifier input and allows the use of low-cost high-power multi-mode pump lasers. Although many research groups have recently demonstrated cladding-pumped multi-core amplifiers [3][4][5][6][7][8][9], one drawback of this technology remains its low pumping efficiency. How pumping efficiency translates into power efficiency depends on the specific amplifier designs, for example the number of cores in the cladding pumped amplifier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multi-core transmissions, cladding pumping avoids spatial channel demultiplexing/multiplexing at the amplifier input and allows the use of low-cost high-power multi-mode pump lasers. Although many research groups have recently demonstrated cladding-pumped multi-core amplifiers [3][4][5][6][7][8][9], one drawback of this technology remains its low pumping efficiency. How pumping efficiency translates into power efficiency depends on the specific amplifier designs, for example the number of cores in the cladding pumped amplifier.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite the narrow cross-sections, wide band amplification can be achieved in EYDFAs by operating an amplifier in highly saturated conditions, leading to high gain toward the longer wavelengths, while the gain remains insufficient below 1535 nm. Using this principle, multiple MC-CP-EYDFAs have been demonstrated for wideband amplification [6][7][8][9]27]. In order to make Er/Yb-co-doped fiber amplifiers compatible with current communication networks, it is required to operate them with a flat gain over the entire C-band.…”
Section: Introductionmentioning
confidence: 99%
“…A spatially integrated optical amplifier sharing the same pump is also of interest for applications requiring a compact solution for switching and routing [9]. Although initial work on multi-core erbium-doped fiber amplifiers (MC-EDFAs) used in-core pumping, there is a growing interest in cladding-pumped MC-EDFAs [10][11][12][13][14][15][16][17][18]. Erbium-doped fiber amplifiers (EDFAs) with in-core pumping are well-known for their high performance in terms of gain, noise, optical bandwidth and power efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems cost and power savings can be realized by using integrated multicore cladding pumped amplifiers 1 . Cladding pumped multicore amplifiers require only one multimode laserdiode for amplification of all cores, making them relatively smaller in size and attractive for commercial applications 2 .…”
Section: Introductionmentioning
confidence: 99%
“…16QAM, 32QAM, 64QAM, etc. 2 . To maximize the throughput over a given multicore transmission system, the order of the QAM formats can be adapted for each wavelength channel as well as for each core according to the available SNR at the receiver.…”
Section: Introductionmentioning
confidence: 99%